Management Design and Construction of Electric Power Monitoring Electrical Design Laboratory Bandung State Polytechnic With Powertag - Tohir, Toto; Wijayanti, Linda; Mulyadi, Melisa; Anwar, Hadrian; Kumar, Saurav (The International Journal of Education Management and Sociology, 2024)
The Electrical Design Laboratory is a facility where lecturers and students carry out various experiments, research and developments related to electricity. Monitoring electrical power can be a very smart move to manage expenses and also help reduce environmental impact. Electrical power usage that is not directly monitored during peak loads will result in excessive power usage. Therefore, MCB trips often occur in electrical design laboratories on switchboards with high loads, so the ability to monitor electric current usage is required. The PowerTag system was introduced to meet this tracking need for controlling Air Conditioning, Incandescent Lamps, Heaters, Dispancers and Vacuum Cleaner loads. The system is connected to the load to determine the magnitude of electrical parameters such as power, voltage, current, power factor, and then these parameters will be sent via the Zigbee communication protocol to the Concentrator. The concentrator receives data from PowerTag and then forwards it to a local server using the Modbus TCP/IP communication protocol to then be processed to the HMI for presenting data resulting from monitoring the system. The aim of this research is to design a tool that can detect current, voltage, power, power factor and frequency in real time. The research results show that the current flowing in the neutral conductor is 4.46 A and 6.69 A